Beyond Batik Lasem: Utilizing Instagram for MSMES’ Growth Opportunity and Challenges - Tinjung Desy Nursanti; Evy Steelyana; Ine WawoRuntu (Bina Nusantara University, 2024)
The research explored the distinctive attributes and unique impact of Lasem’s online batik shops on the development, cultural preservation, and women’s empowerment of Micro, Small, and Medium Enterprises (MSMEs). Employing a descriptive qualitative method, the researchers integrated theories of women’s empowerment, local economic development, and cultural preservation to analyze data. Data were collected through in-depth interviews, participatory observations, and document studies. Meanwhile, thematic analysis was conducted, involving data coding, categorization, and interpretation. The findings indicate that Lasem’s online shops, which hold daily, weekly, or spontaneous Instagram live sales sessions, significantly influence these areas. These shops highlight the town’s cultural heritage and leverage its Internet infrastructure. The research reveals substantial employment of women of all ages in Lasem’s online batik sector, emphasizing platforms that teach skills and promote economic independence. Live sales attract foreign clients, enhancing Lasem’s global reputation and promoting tourism and cultural preservation despite its remote location. Results show that the Instagram live sales environment is modest but growing, with most online shops offering frequencies. Social media participation by women significantly boosts financial independence and skill development. Live sales events also draw international buyers, and online marketing promotes Lasem’s culture. The research supports several Sustainable Development Goals (SDGs): Decent Work and Economic Growth (SDG 8) through skill development and income generation for women; Industry, Innovation, and Infrastructure (SDG 9) through digital marketing for cultural preservation and tourism; and Sustainable Consumption and Production (SDG 12) through quality packaging and ethical consumption. These efforts enhance economic empowerment, cultural sustainability, and responsible consumerism.